The role of empathy in shared intentionality: Contributions from Inter-Processual Self theory - Luis, Elkin O.; Martínez, Martín; Akrivou, Kleio; Scalzo, Germán; Aoiz, Martín; Orón Semper, José Víctor (Frontiers in Psychology, 2023)
Research in psychology related to the conceptualization of empathy has been on the rise in the last decades. However, we argue that there is still space for further research to help capture the important notion of empathy and its theoretical and conceptual depth. Following a critical review of the current state of the research that conceptualizes and measures empathy, we focus on works that highlight the importance of a shared vision and its relevance in psychology and neuroscience. Considering the state of the art of current neuroscientific and psychological approaches to empathy, we argue for the relevance of shared intention and shared vision in empathy-related actions. Upon review of different models that emphasize a shared vision for informing research on empathy, we suggest that a newly developed theory of self, human growth and action–the so-called Interprocessual Self theory (IPS)–can significantly and novelly inform the theorization on empathy beyond what the literature has stated to date. Then, we show how an understanding of integrity as a relational act that requires empathy is an essential mechanism for current key research on empathy and its related concepts and models. Ultimately, we aim to present IPS as a distinctive proposal to expand upon the conceptualization of empathy.